2003
DOI: 10.3346/jkms.2003.18.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Recently Occurring Adult Tetanus in Korea: Emphasis on Immunization and Awareness of Tetanus

Abstract: Since a nationwide childhood vaccination with tetanus toxoid, tetanus has become a rare disease in Korea. However, we recently experienced 17 cases of adult tetanus in a university hospital during a 21-month period. Seventy percent of the patients were female, and the mean age was 63 yr (range, 29-87). The majority (88.2%) of the patients did not get primary vaccinations for tetanus and decennial tetanus-diphtheria toxoid booster. Most patients (88.2%), who sustained acute injury, did not seek medical care for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…There are quite a number of elderly people with low serum levels of tetanus in Korea, and the mean age of the onset of tetanus infection was 63.3 years in the 17 cases reported in the early 2000s in Korea 15. As mentioned, the tetanus seroprevalance of adults older than 41 years is lower than 40%, and therefore, decennial Td vaccination should be encouraged in Korea 1213…”
Section: Discussionmentioning
confidence: 97%
“…There are quite a number of elderly people with low serum levels of tetanus in Korea, and the mean age of the onset of tetanus infection was 63.3 years in the 17 cases reported in the early 2000s in Korea 15. As mentioned, the tetanus seroprevalance of adults older than 41 years is lower than 40%, and therefore, decennial Td vaccination should be encouraged in Korea 1213…”
Section: Discussionmentioning
confidence: 97%
“…There was a temporary decrease in DTaP coverage because of misunderstood contraindications of the vaccine and exaggerated reports of unconfirmed adverse events. Under these circumstances, around 10 cases of tetanus were reported annually in Korea ( 15 ) and one case of polyneuropathy assumed to be caused by a diphtheria infection was reported ( 16 ). Because immunity against diphtheria and tetanus wanes in the absence of routine administration of booster vaccinations among adolescents and adults, cohorts of susceptible people increase.…”
Section: Discussionmentioning
confidence: 99%
“…15e17 The DTaP immunization coverage rate of >95% resulted in a decrease in the prevalence of diphtheria and neonatal tetanus, and no cases of diphtheria have been reported since 1987 in Korea. 15 About 10 cases of tetanus have been reported annually in Korea, 18 and one case of polyneuropathy that was assumed to be caused by a diphtheria infection was reported. 19 However, previous seroepidemiological studies in Korea reported that most of the studied participants older than 40 years had antibodies against diphtheria and tetanus at < 0.1 IU/mL, 16,17,20 suggesting that Td booster vaccination is necessary for adolescents and adults to maintain long-term protective immunity against diphtheria and tetanus.…”
Section: Discussionmentioning
confidence: 99%